Physico-chemical characteristics of fine fraction materials from an old crystal glass dumpsite in Sweden. Issue 9 (21st October 2019) - Mutafela, Richard N.; Marques, Marcia; Jani, Yahya; Kriipsalu, Mait; Hogland, William
ABSTRACT : Physico-chemical characteristics of waste, particularly fine fraction (FF), from an old crystal glass waste dump in Sweden were studied to assess recycling or disposal alternatives. Hand-sorting of the waste indicated glass content of 44.1% while sieving established the FF as a more soil-like mix of glass and other materials constituting 33.3% of all excavated waste. The FF was around neutral pH with 24.4% moisture content, low values of Total Dissolved Solids, Dissolved Organic Carbon and fluorides, but hazardous concentrations of As, Cd, Pb and Zn according to the Swedish Environmental Protection Agency guidelines. While the FF leached metals in low concentrations at neutral pH, it leached considerably during digestion with nitric acid, implying leaching risks at low pH. Thus, the waste requires safe storage in hazardous waste class 'bank account' storage cells to avoid environmental contamination as metal recovery and other recycling strategies for the glass waste are being developed. The study could fill the information gap regarding preservation of potential resources in the on-going, fast-paced excavation and re-landfilling of heavy metal contaminated materials in the region.